Serving IPV Survivors in Culturally Diverse Communities: Perspectives From Current Service Providers - Taylor, Sarah (Violence against women, 2024)
This qualitative study examines current IPV service providers’ perspectives on service delivery methods that best reach and serve IPV survivors from culturally diverse communities. Semi-structured interviews were conducted with 11 service providers, and transcripts were analyzed for themes related to service providers’ experiences. Five themes emerged from the data that suggest best practices for reaching and serving survivors from culturally diverse backgrounds, including understanding survivors’ backgrounds, promoting trust and inclusivity, building community relationships, providing culturally responsive education on IPV, and supporting current and future staff with training. Study findings provide implications for the education and training of future service providers.